(untitled) (The Research of Medical Science Review, 2025)
This review examines the correlation between fast food intake and the increased risk of obesity and chronic diseases, emphasizing the nutritional elements that contribute to these health concerns. Fast food, typically characterized by high caloric density, excessive unhealthy fats, refined carbohydrates, and elevated sodium levels, has become a fundamental component of numerous diets owing to its convenience, cost-effectiveness, and extensive accessibility. Nonetheless, its regular intake is linked to various detrimental health effects, including obesity, cardiovascular illnesses, type 2 diabetes, and mental health difficulties. This article examines the worldwide increase in fast food consumption, identifying demographic variables, marketing methods, and lifestyle alterations as the primary catalysts of this phenomenon. It further examines the nutritional composition of fast food, highlighting the contribution of imbalanced diets to the development of obesity and chronic diseases. This review examines the psychological effects of fast food, including emotional eating, and its association with mental health disorders. This review ultimately recommends several preventive measures and interventions, such as public health campaigns, regulatory modifications within the fast-food sector, and individual behavioral changes, as techniques to mitigate the adverse health impacts of fast-food consumption. This review highlights the pressing need for international efforts to address escalating health issues linked to fast food consumption and foster healthy eating habits.